2000
DOI: 10.1097/00003246-200001000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Physiology and Chronic Health Evaluations II and III and Simplified Acute Physiology Score II: A prospective cohort study evaluating these methods to predict outcome in a German interdisciplinary intensive care unit

Abstract: Our data more closely resemble those of the APACHE II database, demonstrating a higher degree of overall goodness-of-fit of APACHE II than APACHE III and SAPS II. Although discrimination was slightly better for the two new systems, calibration was good with a close fit for APACHE II only. Hospital mortality was higher than predicted for both new models but was underestimated to a greater degree by APACHE III. Both score systems demonstrated a considerable variation across the spectrum of diagnostic categories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
65
1
10

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 35 publications
10
65
1
10
Order By: Relevance
“…6,[7][8][9][10][11] There was a higher frequency of trauma (15%) in relation to American and European studies, but this was similar to what has already been found in Brazil, 7,10,12 The patient distribution in the APACHE II score intervals showed highest concentrations in the intermediate ranges, coinciding with what was found by other authors. 8,10,13 However, the percentage of patients with APACHE II scores of less than 10 (22.4%), and thus with less severe illness conditions, was much lower than for the US study, 56%.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…6,[7][8][9][10][11] There was a higher frequency of trauma (15%) in relation to American and European studies, but this was similar to what has already been found in Brazil, 7,10,12 The patient distribution in the APACHE II score intervals showed highest concentrations in the intermediate ranges, coinciding with what was found by other authors. 8,10,13 However, the percentage of patients with APACHE II scores of less than 10 (22.4%), and thus with less severe illness conditions, was much lower than for the US study, 56%.…”
Section: Discussionsupporting
confidence: 80%
“…Although APACHE II was one of the first systems described, it is still the most widely used of them, insofar as the data required for its calculation are simple, well defined, reproducible, and collected on a routine basis during intensive care service provision.In Brazil, it is used by the Ministry of Health as a criterion for classifying intensive care units. 5 Markgraf et al 6 compared the predictive capabilities of APACHE II, APACHE III and SAPS II and concluded that the three indices have good discriminating power and that APACHE II has the best calibration. For this reason, it scored the most accurate mortality prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Jubran et al confirmed that the comorbidity score might increase mortality by 24% [18]. Finally, APACHE II was found to be a better predictor of mortality compared to SAPS II in patients with respiratory disease in ICUs (AUCOC = 0.81) [19], as well as having a higher diagnostic accuracy compared to APACHE III and SAPS II in German interdisciplinary ICUs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from developing countries also reported good calibration of PIM2 score, such as a study from Trinidad (X2=5.61, df=8, p=0.69) done by Hariharan [4]., and a study from Barbados (X2=5.64, df=7, p=0.58) done by Hariharan [38], and in Al Fayoum University a study done by Bekhit [37] found (H-L X2= 1.410, df= 8, p=0.9) well calibration, while in Italy by Atti [29] Calibration was less satisfactory (114.7 vs. 53; p < 0.001). Difference in results of discrimination, calibration and SMR among different studies has been attributed to various factors like poor performance of medical system in developing countries where resources are more limited [12], different case mix [42], disease pattern [43] and failure of the scoring system equation to model the actual situation accurately [44]. In our study, PIM2 score on day of admission showed significant positive correlation with risk of mortality with acceptable discrimination ability (area under ROC curve 0.73), and good calibration (p=0.88).…”
mentioning
confidence: 99%